Determinants and problems of well-being of farming population in Poland and local social innovations in rural areas - Dudek, Michał; Mróz, Agata; Wilczyńska, Elwira; Komorowski, Łukasz (Bulletin of Geography. Socio-economic Series, 2025)
The article aims to identify the determinants of well-being of the farming population in Poland. The paper also presents ways to improve the quality of life of farmers through social innovations implemented in Tuchola county and in five municipalities of Hajnówka and Białystok counties. The study was primarily based on a literature review and research materials mainly from individual in-depth interviews and focus group interviews conducted with farmers and key informants. Initial research revealed several specific determinants affecting farmers’ well-being; subsequent analysis enabled them to be grouped into four broad categories: spatial and temporal access to health and social services; access to internet and digital solutions; farm succession; and levels of trust and cooperation. Finally, each specific determinant was then mapped to the components of well-being (physical, mental, social) that it impacted most directly. In-depth analysis showed that social innovations related to diversifying farmer’ activities, integrating them with the local community, and offering mobile social and healthcare services were solutions that positively influence farmers’ well-being.